FROM ELIZABETHAN PLAYHOUSES TO SITE-SPECIFIC THEATRE: TRACING THE GENEALOGY OF IMMERSIVE THEATRE AND THE REIMAGINED SPECTATOR - Parashar, Ms. Mrigakshi (ShodhKosh: Journal of Visual and Performing Arts, 2024)
This paper traces the historical evolution of immersive theatre by examining its genealogical roots in Elizabethan playhouses and progressing through various theatrical movements that prioritized spatial dynamics and audience engagement. Situating immersive theatre not as a rupture but as an evolution, the study examines how the shifting boundaries between performer and spectator mirror broader socio-cultural transformations in class, power, embodiment, and subjectivity. Drawing upon performance theory, scenographic history, and neoliberal critiques, the paper argues that immersive theatre functions as a site of embodied spectatorship and affective agency—where the spectator is no longer merely a viewer, but a co-creator of meaning. By foregrounding participation, risk, and spatial intimacy, immersive practices enact a rupture in theatrical convention while simultaneously offering new modes of social interaction and self-awareness. This genealogical approach reveals immersive theatre as a dynamic form deeply embedded in historical practices of ritual, rebellion, and relationality. By contextualizing immersive theatre within a broader historical continuum, the paper reveals how spatial dramaturgy and the reconfiguration of audience roles have consistently re-emerged to challenge traditional theatrical norms, culminating in the multi-sensory, participatory experiences that define immersive theatre today